Ergonomic Risk Assessment and Fatigue Analysis During Manual Lifting Tasks in Farming Activities (International Journal of Occupational Safety and Health, 2024)
Introduction: Farming is a physically demanding occupation that puts farmers at risk of musculoskeletal disorders, particularly when frequently performing activities like heavy lifting, which strains the lower back muscles. The present study aimed to assess the ergonomic risk and fatigue during manual lifting tasks pertaining to farming activities.Methods: A study was performed on 20 farmers to analyze the ergonomic risks associated with load lifting through the estimation of the Recommended Weight Limit and Lifting Index using the revised NIOSH lifting equation. The low back compression forces of the participants were estimated using the 3DSSPP software. Surface electromyography was employed to analyze the onset of muscle fatigue during the lifting activity.Results: The results of the study showed a 111.12% increase in the recommended weight limit, a 52.77% reduction in lifting index, and a 28.15% reduction in the low back compression forces for the redesigned lifting technique. The average low-back compression force for the redesigned technique was observed to be well below the back compression design limit of 770 lb. A reduction in the slope of the RMS voltage regression line by 60% and a reduction of 50.23% in the peak spectral power of the sEMG signal, accompanied by a shift in the peak spectral power towards higher frequency region indicated delayed onset of fatigue for the redesigned technique.Conclusion: The outcomes of the study indicated that the ergonomic redesign of the lifting task could significantly reduce the lifting index and alleviate the spinal compression forces well within the back-compression design limit. The redesign was also found to delay the onset of fatigue in the erector spinae muscles.